Analisis Perbandingan pada Puisi "Tentu, Kau Boleh" Karya Sapardi Djoko Damono dengan Puisi "Anant Prem" Karya Rabindranath Tagore - Anggoro, Ari; Saputra, Fajar Anggi; Pratama , Dimas Ageng (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This study aims to analyze and compare the poems Anant Prem by Rabindranath Tagore and Tentu, Kau Boleh by Sapardi Djoko Damono. The research employs a descriptive qualitative approach focusing on several literary aspects, namely the central theme, tone and atmosphere, diction, characterization, conceptual meaning of love, and philosophical perspective. The findings indicate that both poems share similarities in presenting love as a profound emotional experience, expressed through intimate and reflective nuances. Each poem portrays emotionally intertwined characters whose inner experiences revolve around the presence of love as a central force. Despite these similarities, the two poems differ significantly in how they interpret and narrate love. In Anant Prem, Tagore frames love as eternal and transcendent, surpassing the confines of time and space. This creates a contemplative and spiritual tone supported by metaphorical and symbolic diction. Meanwhile, Tentu, Kau Boleh portrays love as an immediate and personal experience rooted in everyday human interactions. Sapardi expresses love through calm, straightforward language that reflects simplicity and emotional closeness. Philosophically, Tagore positions love as part of cosmic existence, whereas Sapardi views it as a presence embodied in the warmth and intimacy of daily human life. These distinctions highlight how cultural background, worldview, and poetic tradition influence the depiction of love in both works.